Epidemiological profile of snake bite at tertiary care hospital, East India - Srivastava, Anubha; Gupta, Animesh; Singh, Sanjay K. (International Journal of Advances in Medicine, 2017)
Background: Snakebite is a common medical emergency and an occupational hazard for majority of Indian population especially farmers. Epidemiological data on snake bite from the East India is sparse. Methods: This hospital based prospective study was conducted from March 2013 to February 2014. 200 cases of snakebite poisoning were admitted to the hospital during the study period. Results: Majority of victims belonged to the age group of 15-45 (60%), resident of rural areas (92%) and were involved in agricultural activities (60%). The study population was predominately bitten outdoors (66%), in the lower extremity (86%), at night (82%). Respiratory muscle paralysis (66.7%), ptosis (66.7%), coagulopathy (60%), acute renal failure (55.6%), shock (55.6%) were the signs associated with poor prognosis. Conclusions: Snakebite is an important occupational hazard, though preventable in principle remains to be one of the common medical emergencies.